Cultural Conflicts: How to Overcome Them? - SULISTIANINGSIH, Dewi; PRABOWO, Muhammad Shidqon; PUJIONO, Pujiono (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019, 2019)
The purpose of this article is to present a comprehensive analysis and study of cultural conflicts that occur in Indonesia, especially in West Kalimantan. The method used in this study is a legal research method with the type of qualitative research. The main focus of this paper is to study how the law can play a role in creating a conducive atmosphere to support the resolution of cultural conflicts that have occurred in Indonesia. This paper uses a critical analysis method by collecting, presenting and referring to argument discussions that are in favor and against the resolution of cultural conflicts in conflict-prone areas in Indonesia. This paper aims to raise cultural awareness for the community in Indonesia to prevent conflicts from taking places due to cultural differences and lack of understanding of the awareness of multiculturalism particularly through education. In addition, this paper also describes the role of the state in managing the social conflicts that have occurred in Indonesia. Indonesia is a pluralistic country having a variety of ethnics, religions, languages, cultures, etc. Such variety is a beneficial asset for Indonesian, but it also has great potential to generate conflicts. There are several inter-ethnic conflicts which have occurred in Indonesia, such as: Dayak-Madura conflict in Central Kalimantan, the Poso Case in Sulawesi Tengah, etc. Multiculturalism education is crucial in conflict-prone areas especially for the younger generation, starting from the primary to the secondary high education. This can be done by the Education Office as well as the government parties in charge of upholding the supremacy of law through inter-sectoral cooperation.